Implementation of Good Governance in Komodo National Park Management: A Case Study - Sudiartha, I Gde; Sudana, I Putu; Dwirandra, Anak Agung Ngurah Bagus; Wirajaya, I Gde Ary (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 2 (2021), 2021)
This study examines the implementation of good governance at the Komodo National Park to provide a specific, in-depth, complex, and explorative understanding of it. The research methodology used was a descriptive interpretive Yin case study approach. Data were obtained through observation, interviews, and documentation. The results revealed that the Komodo National Park applies the principles of good governance, transparency, accountability, responsibility, independence, and fairness. Study findings also contribute benefits, ideas, and studies, which provide reference for and contribution to the management and stakeholders in conducting governance roles, especially for National Park management.  Keywords :   good governance, management, national park